The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1088/0967-3334/21/4/201
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of impedance to assess myocardial contractility and rhythm stability

Abstract: By introducing an alternating current through the ventricular cavity via a multipolar catheter the potential difference measured between adjacent electrodes can be used to assess ventricular volume. This is possible by the measurement of intracardiac impedance. The data obtained can be used to construct pressure-volume loops allowing the continuous real-time assessment of myocardial contractility. Clinical applications of this research tool are now becoming apparent. Further derivations of impedance measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Alternating current (AC) elds are widely used in cardiac research. A study by Arthur et al 1 demonstrated that delivery of AC stimulus through intraventricular catheters can determine ventricular volume, and thus assess myocardial contractility in vivo. Warren et al 2 measured myocardial impedance using AC elds to determine areas within the myocardial wall that had healed following damage due to an infarction.…”
Section: Introductionmentioning
confidence: 99%
“…Alternating current (AC) elds are widely used in cardiac research. A study by Arthur et al 1 demonstrated that delivery of AC stimulus through intraventricular catheters can determine ventricular volume, and thus assess myocardial contractility in vivo. Warren et al 2 measured myocardial impedance using AC elds to determine areas within the myocardial wall that had healed following damage due to an infarction.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of 1247 patients showed there was no association between LVEF and septic shock mortality [ 32 ]. The left ventricular pressure-volume conductivity catheter provides another method to measure real-time cardiac function, making the quantitative measurement of systolic and diastolic function correspond more to the criterion standard; however, the significance of this method to SIMD needs further verification [ 33 ]. Serum cardiac biomarkers could provide independent information related to cardiac function.…”
Section: Discussionmentioning
confidence: 99%